Riemann Problem for a Combustion Model System: the Z-N-D Solutions (Journal of Partial Differential Equations, 2020)
The Riemann problem for a combustion model system with special kind of viscosity and chemical reaction is considered and the existence of the Riemann problem is proved. The limit of the Riemann solution as vanished viscosity is also investigated.